Impacts of permafrost degradation on streamflow in the northern Himalayas - Fan, Linfeng; Ji, Fang; Kuang, Xingxing; Guo, Zhilin; Zhang, Rui; Zheng, Chunmiao (Science China Earth Sciences, 2024)
The Himalayan water tower provides crucial water resources for Asia. Permafrost degradation is deemed to exert important impacts on streamflow in the Himalayan rivers. Yet, the magnitudes of such impacts remain poorly quantified. Here, we established a robust hydrological model that incorporated active layer deepening and ground ice melt for the drainage basin of the largest river in the northern Himalayas-the Yarlung Zangbo River (YZR). We estimated that permafrost degradation led to similar to 0.65 km3/yr decrease in surface runoff and similar to 0.35 km3/yr increase in baseflow and ground ice melt contributed similar to 0.25% to the annual streamflow in the YZR for the period 2001-2022. The "fill-and-spill" mechanism helps explain the seeming contradiction of observed increasing versus decreasing baseflow in different permafrost regions worldwide. We propose that the dilution of riverine dissolved organic carbon (DOC) concentrations by baseflow may lead to the riverine DOC hysteresis patterns. This study not only lays solid scientific basis for water resources management in the Himalayas, but also yields new insights into how to interpret measured river discharge and nutrient flux in permafrost regions over the globe.